2019
DOI: 10.1111/radm.12369
|View full text |Cite
|
Sign up to set email alerts
|

Non‐R&D innovation and firms’ new product performance: the joint moderating effect of R&D intensity and network embeddedness

Abstract: Non-R&D innovation increasingly plays a critical role in explaining firms' new product performance. Yet, there has been little research on the consequences and contingent mechanisms of non-R&D innovation for firms embedded in collaborative network environments. To address this research gap, we investigated a conceptual framework of non-R&D innovation using data drawn from Chinese manufacturing firms. First, we found that non-R&D innovation positively affects firms' new product performance. Second, we discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…Empirical literature has suggested that network embeddedness influenced various aspects of firms' innovation (Xie et al, 2019;Pauget and Wald, 2018;Wang and Chen, 2012;Rutten and Boekema, 2007;Grewal et al, 2006). Even in a clutter with geographical proximity and homogeneity, the innovation performances of the members varied, and network embeddedness was found to be a key contributor (Gebreeyesus and Mohnen, 2013).…”
Section: Literature Review 21 Network Embeddedness and Innovation Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Empirical literature has suggested that network embeddedness influenced various aspects of firms' innovation (Xie et al, 2019;Pauget and Wald, 2018;Wang and Chen, 2012;Rutten and Boekema, 2007;Grewal et al, 2006). Even in a clutter with geographical proximity and homogeneity, the innovation performances of the members varied, and network embeddedness was found to be a key contributor (Gebreeyesus and Mohnen, 2013).…”
Section: Literature Review 21 Network Embeddedness and Innovation Performancementioning
confidence: 99%
“…In the high-tech industry, Lyu et al (2019) found that at the initial and growth stages of industrial technology development, the centrality and network reach of a firm's network embeddedness exert a positive impact on the inbound open-innovation practice. Studying manufacturing firms, Xie et al (2019) found that network embeddedness significantly enhanced the relationship between research and development intensity and new product performance. On a regional level, Rutten and Boekema (2007) found that norms, values and customs of regional networks facilitate collaboration for mutual benefit of innovation firms.…”
Section: Introductionmentioning
confidence: 99%
“…Some significant benefits of adopting a social network view of an innovation network are rooted in the key tenets of network embeddedness (Mitsuhashi and Min, 2016; Xie et al , 2019). Network embeddedness, commonly found in social and organizational research, asserts that organizational performance is largely dependent on its structural relationships with other organizations that are embedded together in the network (Choi and Kim, 2008; Nair et al , 2018).…”
Section: Theories and Hypothesesmentioning
confidence: 99%
“…First, for the focal firm with high technological proximity to other peers, occupying a central position will gain additional stimulus in fostering incremental innovation capability during the external innovation search activities (Buchmann and Kaiser, 2019; Wincent et al , 2009). On the one hand, firms that are more centrally embedded in their innovation networks will be in better positions to exploit partner’s technology and knowledge, as well as accumulate more external sources, which is essential to help them develop incremental innovation capabilities (Mazzola and Perrone, 2013; Xie et al , 2019). On the other hand, higher technological proximity to other peers would increase the focal firm’s abilities to leverage and absorb the relevant resource in an existing knowledge domain (Liu and Ma, 2019) and promote the recombination of knowledge within its dominant design, thereby facilitating its incremental innovation capability (Guan and Yan, 2016).…”
Section: Theories and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation